Contractual capacity and the conflict of laws in common-law jurisdictions (part 1) : the United Kingdom - Fredericks, Eesa A. (Obiter, 2018)
This series of two articles provides a comparative overview of the position in the common-law conflict of laws in respect of the contractual capacity of natural persons. The comparative study is undertaken in order to provide guidelines for the future development of South African private international law. Reference is primarily made to case law and the opinions of academic authors. The legal position in the law of the United Kingdom, as the mother jurisdiction in Europe, is investigated in part I. Although Scotland is a mixed civil/common-law jurisdiction, the situation in that part of the United Kingdom is also discussed. Part II will deal with the rules and principles of private international law in respect of contractual capacity in Australasia (Australia and New Zealand), North America (the common-law provinces of Canada and the United States of America), Asia (India, Malaysia and Singapore) and Africa (Ghana and Nigeria). Part II also contains a comprehensive summary of the legal position in the common-law countries, followed by ideas for the reform of South African private international law in this regard.

Impact of Contractual Capacity of Minor - Godha, Atisha (International Journal of Trend in Scientific Research and Development, 2018)
A contract involves s a promise between two persons for the exchange of either good or services. A contract signifies the free consent of the parties to the contract to be bound by law. For a contract to be valid, it must have these basic elements: mutual assent, consideration, capacity, and legality. Mutual assent is characterized by offer and acceptance through mutual accent; "consideration," on the other hand denotes any form of compensation with something of value for the goods or services traded. A contract between persons, either natural persons or legal persons, who have no capacity to contract can either be voidable or void depending on the case. Legality gives the condition that should be satisfied for a contract to be excised by the law. Illegal contracts are for example those involving illegal activities. For example one can't bring a plea of damages to a court of law for breach of a contract entered into to kill another person.The possible remedies for breach of contract are; general damages, consequential damages, reliance damages, and specific performance. This paper will examine the capacity to contract as pertains to contracts entered by minors minor's.
Keywords: Capacity; Consideration; Contract; Legality; Minor; Mutual accent void/voidable

Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
Keywords: Contract; Locatio conductio

Water as public property : a parallel evaluation of South African and German law - Viljoen, Germarié (North-West University, 2016)
With the introduction of the National Water Act 36 of 1998 (NWA) in South Africa’s water regulatory regime, the foundations of the country’s existing water law system changed fundamentally. The NWA was promulgated with the primary aim to reform the law relating to water resources. The preamble to the NWA states that water is “a scarce natural resource that belongs to all people.” Section 3 of the NWA continues along similar lines and stipulates that all water use rights fall under the centralised control of the state or public trustee to inter alia improve the distribution, management, use, conservation and equality of access to this scarce resource. Statutory transformation of this nature has inevitable and important legal implications. It has for example been argued that the changed system has brought about a reallocation and redefinition of property rights to natural resources; a transformation which will inevitably impact the nature, form, extent, limits and protection of access and use rights that can be acquired in water as a natural resource. In an effort to understand the extent of the legal transformation brought about by the concept of public trusteeship, this thesis considers the impact of the concept in the broader South African water law context. The concept of public trusteeship is a novel concept in South African jurisprudence, without established links to existing principles of law. This thesis subsequently focuses on how and to what extent the German property law concept of őffentliche Sache may inform the development and interpretation of the South African concept of public trusteeship as entrenched in the NWA. Consequently, this thesis commences with an exposition of information on the idea of property and the relevance and importance of the different property rights regimes against which both the South African and German property regimes can be evaluated. This is followed by a description of the South African property rights paradigm and its different property concepts. The research introduces a novel take on the discussion of the regulation of rights in natural resources in South Africa, namely a “stewardship ethic of public trusteeship”. As a stewardship ethic could potentially influence the regulation of property in natural resources and even perhaps the property regime within which water as natural resource is regulated in South Africa, the next section of the research proceeds with a historical account of the South African water law dispensation. Although the historical review indicates that the concept of public trusteeship is not part of South Africa’s common law heritage, some of its principles find application in the common law concept of res publicae. The conclusion is that the concept of public trusteeship does not merely (re-) introduce the res publicae concept into the South African water realm. The concept of public trusteeship is a novel concept that was statutorily introduced into the South African water regulatory framework in terms whereof “ownership” of water resources vests in the national government, and are consequently administered on behalf of the nation and generations yet to come. A separate section of the research analyses and contextualises the concept of őffentliche Sache as it functions in German law to offer new insight into the implications that the statutorily introduced concept of public trusteeship might have on water as property and the property regime within which water is regulated in South Africa. This guides the study to the next section of the research, which illustrates that the concept of őffentliche Sache is at the basis of the German water regulatory framework. The conclusion of the study proposes an understanding of the concept of public trusteeship in South Africa based on lessons learned from the German concept of őffentliche Sache.
Keywords: Constitutional property; German water regulatory framework; National Water Act; Property; Property rights regime; Public property; Public trusteeship; Res publicae; Water rights; Öffentliche Sache

The regulatory function of contract law : comparative law and economics approach - Gramcheva, Lyubomira (European University Institute, 2015)
This thesis challenges the traditional view of national contract laws as facilitative regimes and argues that contract law on the national level has been progressively re-oriented to perform an efficiency-driven regulatory function. To develop the argument the thesis studies the contract law remedial regime of two common law and one civil law jurisdiction – the US, England and Bulgaria, in two specific contracts – the sale-of-goods and the construction contract. The introductory chapter puts the main theme in context and outlines the project. Exploring the limits of promissory theory and neoclassical economics, the second chapter develops an innovative interdisciplinary methodology joining the new institutional economics with the comparative law method. The third, fourth and fifth chapters offer taxonomies of remedies, types of contracts and remedial effects to set the stage for a meaningful comparison across the different legal traditions. Since economic theory has advanced most in the study of incentives generated by damages, the third chapter focuses on the latter remedy and shows that the common law classification of damage measures (expectation, reliance, restitution), on which traditional law-and-economics accounts are based, can be applied to study a civil law jurisdiction like Bulgaria. Distinguishing discrete and long-term contracts and demonstrating that the differentiation between sale-of-goods and construction contracts in the compared national legal systems does not necessarily go along the lines of the discrete/long-term distinction in economics, the fourth chapter argues that the positive comparison should be made with an eye on the market for substitute performances even if the compared factual scenarios are classified under different legal categories in the different jurisdictions. For the uninitiated, the fifth chapter reconstructs and criticises the standard economic model rationalising damages as incentives. The final chapter applies the approach developed here to contractual termination. The exemplary analysis identifies trends in the compared legal systems and suggests that all of them converge in charging the termination remedy with a regulatory function. Finally, I generalise to make some bolder claims about contract law.
Keywords: Contracts; Law and economics; Public law (Economic aspects)